(untitled) (Faridpur Medical College Journal, 2025)
Tinnitus, a common yet debilitating condition, is linked to factors like hearing loss, ototoxic drugs, head injuries, and depression. The mechanisms behind tinnitus remain unclear, though inner ear pathology, auditory nerve issues, and central nervous system abnormalities are involved. A review of 15 studies identified noise exposure, age, and hearing loss as common causes. Diagnostic tests, including pure tone audiometry, Otoacoustic emission, auditory brainstem responses, and imaging (fMRI, MRI, PET) are useful but show significant variability. Standardized diagnostic methods are needed to better understand and treat tinnitus. Faridpur Med. Coll. J. 2025;20(1): 51-59